INFLUENCE OF ENDOCROWN PREPARATION IN ENDODONTIC TREATED PREMOLARS - Guilarducci, Gabrielle Silva Torres; Carvalho, Marco Aurélio de; Carvalho, Priscilla Cardoso Lazari (CIPEEX, 2024)
Endocrowns are anchored in the pulp chamber in the cervical region of the root and do not require intraradicular preparation. This technique is easy to perform and requires less clinical time when compared to traditional single crowns with posts and cores. The objective of this study was to evaluate the influence of the presence of the ferrule and the preparation length on the biomechanical behavior of endodontically treated premolars. The study factors were: 1. presence of ferrule (with or without) and 2. preparation length for Endocrown (2, 3, and 4 mm). The response variables were: Maximum principal stress (σmax) Mises for all structures involved. The models with a 2 mm ferrule presented the highest values. When observing the compressive stresses, it was found that the highest stress values were found in the models with a 2- and 4-mm ferrule. When evaluating the compressive stress in the crown, there was a smaller difference between the groups, with the highest values occurring in the models without a ferrule. In tensile stresses, the different preparation heights for the Endocrown do not affect the results in the crown and root. In compressive stresses, the different preparation heights for Endocrown do not affect the results in the crown and root, and for both teeth with and without a ferrule, the highest stress values were found in the 4 mm preparations. Within the limitations of an in-silico study, it can be concluded that the tensile stresses at the different preparation heights for Endocrown do not affect the stress concentrations in the crown and root.